Audience Reception of Mental Health Representation in the Film Sleep Call: An Encoding–Decoding Analysis - Widya Annisa; Iman Sumarlan (Sinthop: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2026)
This study examines how audiences interpret representations of mental health in the Indonesian film Sleep Call using Stuart Hall’s encoding/decoding framework. Employing a descriptive qualitative approach, the research draws on in-depth interviews with eight female Generation Z viewers aged 20–25 who watched the film in cinemas or via the Prime Video streaming platform. The data were analyzed through a thematic reception analysis to identify dominant-hegemonic, negotiated, and oppositional decoding positions. The findings indicate that dominant-hegemonic readings largely align with the film’s preferred meaning by framing mental health vulnerability as closely linked to economic pressure, illegal online lending, and digital loneliness. Negotiated readings accept this framing while expanding it to include relational and social dimensions, particularly the role of support systems. Oppositional readings challenge the film’s narrative by foregrounding issues of gender representation and agency, interpreting the portrayal of mental health as embedded within broader representational politics.These findings demonstrate that meanings surrounding mental health in popular cinema are not fixed but are actively negotiated by audiences based on lived experience and ideological positioning. Within the context of a bounded interpretive community, this study contributes to media reception research in Indonesia by clarifying how mental health representations are decoded, contested, and reinterpreted in contemporary film culture.